(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Evaluate the changes in clinical indicators, blood gases, before and after bronchoscopy in patients on mechanical ventilation in the intensive care unit. Subjects and methods: Prospective, with clinical intervention. Select patients on mechanical ventilation in the intensive care unit with a diagnosis of atelectasis and localized lung consolidation on X-ray films. Compare clinical indicators, blood gases, before and after bronchoscopy. Results: 35 patients met the criteria. Patients with traumatic causes accounted for 82.9%; ISS 26.4 points; the average length of stay in intensive care was 18.8 days; with a mortality rate of 17.1%. When performing bronchoscopy, 80% of patients had thick or pus-filled sputum, and 65.7% of patients had evidence of bronchial obstruction. SpO2 and blood lactate values improved significantly before and after 48 hours of bronchoscopy with p < 0.05. Ppeak values decreased, and PO2 values increased significantly from the 3rd hour after bronchoscopy. P/F ratio increased from 214.9 ± 14.16 before bronchoscopy to 344.2 ± 23.09 48 hours after bronchoscopy with p < 0.05. Conclusion: Bronchoscopy in mechanically ventilated patients with atelectasis and consolidation pneumonia resulted in improved respiratory and blood oxygenation indices after the procedure.